Centromere mechanical maturation during mammalian cell mitosis - Lauren A. Harasymiw (Nature Portfolio, 2019)
During mitosis, tension at the centromere occurs from the spindle but the role of centromere mechanics in controlling metaphase tension is poorly understood. Here, the authors report that mechanical stiffnness of the centromere matures during mitotic progression and is amplified specifically at metaphase.